Chloromethyl Glycosides as Versatile Synthons to Prepare Glycosyloxymethyl‐Prodrugs. Issue 9 (24th January 2022) - Elferink, Hidde; Titulaer, Willem H. C.; Derks, Maik G. N.; Veeneman, Gerrit H.; Rutjes, Floris P. J. T.; Boltje, Thomas J.
Abstract: This work investigates the addition of monosaccharides to marketed drugs to improve their pharmacokinetic properties for oral absorption. To this end, a set of chloromethyl glycoside synthons were developed to prepare a variety of glycosyloxymethyl‐prodrugs derived from 5‐fluorouracil, thioguanine, propofol and losartan. Drug release was studied in vitro using β‐glucosidase confirming rapid conversion of the monosaccharide prodrugs to release the parent drug, formaldehyde and the monosaccharide. To showcase this prodrug approach, a glucosyloxymethyl conjugate of the tetrazole‐containing drug losartan was used for in vivo experiments and showed complete release of the drug in a dog‐model. Abstract : Monosaccharides were introduced on drug molecules to improve their solubility, metabolic stability and oral bioavailability. A new chloromethyl glycoside synthon was developed to enable the synthesis of numerous monosaccharide prodrugs.